Association of opioid receptor gene polymorphisms with drinking severity and impulsivity related to alcohol use disorder in a Korean population. (19th April 2019) - Park, Chun Il; Hwang, Syung Shick; Kim, Hae Won; Kang, Jee In; Lee, Sang Hak; Kim, Se Joo
Abstract: Aims: Recent evidence suggests that the opioid system is implicated in the pathophysiology of alcohol use disorder (AUD). We aimed to examine the genetic influence of opioid receptors on susceptibility to AUD and its clinical and psychological characteristics including harmful drinking behavior and various aspects of impulsivity in AUD patients. Methods: Three μ‐opioid receptor gene ( OPRM1 ) variants and two κ‐opioid receptor gene ( OPRK1 ) variants were examined in 314 male patients with AUD and 324 male controls. We applied the Alcohol Use Disorders Identification Test (AUDIT), Obsessive Compulsive Drinking Scale (OCDS), and Alcohol Dependence Scale. AUD patients also completed the stop‐signal task, delay discounting task, balloon analogue risk task, and the Barratt Impulsiveness Scale version 11 (BIS‐11). Results: No significant differences in genotype distributions or haplotype frequencies were found between AUD patients and controls. However, OPRK1 SNP rs6473797 was significantly related to the severity of alcohol‐related symptoms as measured by AUDIT and OCDS and a haplotype containing rs6473797 was also related to OCDS scores in AUD patients. For other psychological traits, OPRM1 SNP rs495491 was significantly associated with scores on the motor subfactor of the BIS‐11. Conclusion: Genetic variations in opioid receptors may contribute to symptom severity and impulsivity in AUD patients.